Mechanical extraction of shea butter: Optimisation and characterisation studies with comparison to other methods of extraction - Elijah Olawale Ajala; Folorunso Aberuagba; Adesoji Matthew Olaniyan; Mary Adejoke Ajala; Oyetunji Babatunde Okedere (Songklanakarin Journal of Science and Technology (SJST), 2019)
Shea butter (SB) production by mechanical extraction (ME) was optimised by box-behnken (BB) experimental design of response surface methodology (RSM). The process parameters studied (with their ranges) were sample weight (100 – 200 g), temperature (60 – 120oC) and duration of applied pressure (10 – 30 min) to optimise the yield of SB. The characteristics of the SB were determined using standard methods and Fourier transform infrared spectroscopy (FTIR). A comparative study of the SB from ME with other methods of extraction was also performed. The optimum 37% (w/w) yield of SB was obtained from 150 g sample of shea kernel at 90oC and 20 min. The R2 (0.9957) obtained from analysis of variance showed that quadratic model of BB fitted the experimental data well. The characteristics of the SB from ME showed non-compromising quality, with a yield greater than that of traditional method but lower than with solvent method. This study showed that the extraction methods affect both yield and quality of SB.